Microleakage of adhesively bonded cervical amalgam restorations - Briso, André Luiz Fraga [UNESP]; Campos, I. T.; Sundfeld, Renato Herman [UNESP]; Rodrigues, A. L.; Pimenta, LAF (Mosher & Linder, Inc, 2002)
Purpose: To evaluate dye penetration in adhesively bonded cervical amalgam restorations. Materials and Methods: the specimens were randomly divided into four groups and the adhesives Prime & Bond 2. 1, Prime & Bond 2.1 Dual Cure, Scotchbond Multi Purpose Plus and Amalgambond Plus were tested. After being restored and polished, the teeth were thermocycled 1,000 times at temperatures varying between 5degreesC +/- 2degreesC and 55degreesC +/- 2degreesC. Statistical analysis was carried out using the Kruskal-Wallis test and multiple comparisons. Results: Scotchbond Multi-Purpose Plus demonstrated lower levels of microleakage in enamel and dentin. The dual adhesives were more effective than the one bottle adhesive.